Rethinking crisis leadership through leadership-as-practice : A narrative review and future directions - Lehtonen, Salla; Seeck, Hannele; Satama, Suvi; Raelin, Joseph A.; Huhtinen, Aki-Mauri (Elsevier, 2025)
While crisis leadership has received significant attention, existing scholarship lacks an analysis that can account for the collective, embodied and emergent nature of leadership in times of crisis. In this study, we employ a narrative review methodology as the primary analytic tool to synthesise insights on how leadership-as-practice (L-A-P) theory can be applied to crisis leadership, highlighting critical aspects of crisis leadership that are often overlooked by conventional perspectives. Accordingly, we outline three complementary avenues through which L-A-P can enrich crisis leadership research: by (1) enhancing understanding of the dynamic interplay between routines and improvisation, (2) exploring the intersections of leadership and learning during crisis; and (3) capturing collective forms of leadership that emerge under crisis conditions. As a theoretical foray, this study opens avenues for empirical research and offers insights for practitioners in organisations facing complex crises.